Diphtheria Transmission Amid High Immunization Coverage - Adnyani, Ni Kadek Mita Dwi; Subrata, I Made; Adi, Putu Dwi (Universitas Padjadjaran, 2026)
Diphtheria is an infectious disease caused by Corynebacterium diphtheriae that can lead to various complications, including death in individuals with incomplete immunization status. The province of Bali, particularly Jembrana, is an area with high population mobility where diphtheria cases are rarely reported. However, in 2025, one suspected case of diphtheria was identified, necessitating an investigation to determine the source of transmission. The investigation was conducted as a descriptive observational study using a case study approach. Data were collected through field investigations, clinical examinations, and laboratory tests. Based on the investigation results, this was the first reported case in the past three years, occurring on March 13, 2025. The case occurred in Jembrana, the gateway to the island of Bali, which has high population mobility. The patient was a 7 year old boy with a complete immunization status; however, he had a history of close contact with family members who had recently returned from an area with a history of a diphtheria outbreak, making him a potential asymptomatic carrier. Laboratory testing using culture methods yielded negative results, likely due to delayed sample submission and reduced bacterial viability, preventing growth on the culture medium. Under these conditions, the RT-qPCR method has the potential to detect the presence of Corynebacterium diphtheriae DNA even when culture results are negative. Vaccination status acts as a protective factor, but does not completely prevent infection. The most significant factor in transmission is close contact with family members who have a history of travel to areas with diphtheria outbreaks, with the possible involvement of asymptomatic carriers. Management of suspected diphtheria cases requires the immediate administration of Anti-Diphtheria Serum (ADS). These findings underscore the need to strengthen active surveillance, regular monitoring, and public education to prevent an increase in cases.Keywords: Diphtheria, immunization, Corynebacterium diphtheriae, asymptomatic carrier.